Conceptions of Vocational Training in the Works of Lithuanian Educators - Širiakovienė, Asta (Acta Paedagogica Vilnensia, 1997)
Looking through the prism of the history of pedagogy, the paper introduces the basic concepts and trends of vocational training, brought the J.A. Komensky, J.J. Rousseau, J.H. Pestalozzi, G. Kerschensteiner, J. Dewey, K. Marx, V.A. Lay, and others. Most of these trends have had some influence on the development of thought of vocational training in Lithuania. Lithuanian educators, discussing both general and specific issues of vocational training (e.g., manual work in primary grades, school work training – test plot, etc.), quite often relied on the works of aforementioned Western authors. The ideas of vocational training were developed and disseminated in Lithuania by A. Busilas, V. Ruzgas, J. Laužikas, A. Pigaga, A. Paurienė, A. Grabauskienė, and others.